Response Initial Vegetative Growth of Local Durian (Durio zibethinus Murr.) with The Addition of Organic Fertilizers - Sumeru Ashari; Didik Hariyono; Yunita Triliestyana (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2016)
This research aims to observe the three cultivars of durian growth responds using organic fertilizer and to know the suitable type of organic fertilizer in the initial phase of vegetative growth on durian. The research was conducted in the Watulor, Waturejo village, district Ngantang, Malang with altitude 669 meters above sea level with rainfall 1588 mm/year. This research was conducted in February until June 2010. Research were using randomized block design with treatment three types of organic fertilizer 10 kg plant-1 on three local durian cultivars. Treatments were consist of: P1K1 (Durian Jingga using goat manure fertilizer), P1K2 (Durian Arab using goat manure fertilizer), P1K3 (Durian Sepanjang Musim using goat manure), P2K1 (Durian Jingga using chicken manure), P2K2 (Durian Arab using chicken manure), P2K3 (Durian Sepanjang Musim using chicken manure), P3K1 (Durian Jingga using green manure), P3K2 (Durian Arab using green manure), and P3K3 (Durian Sepanjang Musim using green manure).There were 9 treatments and each treatment had 3 repetition. The results of this research showed that in the variable number of leaves, usage of chicken manure and green manure on the Durian Arab had the highest response compared to Durian Jingga and Durian Sepanjang Musim. While in the variable leaf area, Durian Jingga and Durian Arab using chicken and green manure fertilizer was having higher leaf area than Durian Sepanjang Musim. Thesoil analysis of using organic fertilizeron durian showed that the N content in soil was increased, P and K nutrient in the soil was decreased, while the average N content in leaf was decreased, P and K nutrient in the leaves was increased.